1998
DOI: 10.1038/sj.onc.1202292
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-irradiation-induced apoptosis is mediated via ligand independent activation of tumor necrosis factor receptor 1

Abstract: Ultraviolet (UV)-irradiation has been shown to induce jun N-terminal kinase activity via aggregation-mediated activation of tumor necrosis factor receptor 1 (TNFR1) but the role of TNFR1 in mediating UV-induced apoptosis has not been explored. Using p53-null cells, we demonstrate that UV-stimulated ligand independent activation of TNFR1 plays a major role in mediating the apoptotic e ects of UV-irradiation. UV-irradiation and TNFa acted in a synergistic manner to induce apoptosis. UV-irradiation stimulated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 22 publications
5
98
0
Order By: Relevance
“…Even though UV has been shown to be capable of activating membrane death receptors (Kulms et al, 1999;Rehemtulla et al, 1997;Sheikh et al, 1998), we did not ®nd a correlation between UV sensitivity and sensitivity to death receptor signaling. However, it is possible that UV radiation is signaling through another, as yet undetermined, death receptor.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Even though UV has been shown to be capable of activating membrane death receptors (Kulms et al, 1999;Rehemtulla et al, 1997;Sheikh et al, 1998), we did not ®nd a correlation between UV sensitivity and sensitivity to death receptor signaling. However, it is possible that UV radiation is signaling through another, as yet undetermined, death receptor.…”
Section: Discussionmentioning
confidence: 54%
“…It has been shown that UV radiation can activate membrane death receptors and initiate a death signal (Kulms et al, 1999;Rehemtulla et al, 1997;Sheikh et al, 1998). Thus, it was possible that alterations in a death receptor signaling pathway in MDA-MB-468 cells may be responsible for the hypersensitivity of these cells to low doses of UV radiation.…”
Section: Response To Death Receptor Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is convincing evidence that UVB directly activates death receptors including CD95 and the TNF receptor 1 (Aragane et al, 1998;Rehemtulla et al, 1997;Sheikh et al, 1998). Inhibition of death receptor activation by exposing cells at a low temperature (4 -108C) to UVB is associated with a partial reduction in UVB-induced apoptosis.…”
Section: Only Early Application Of Pdtc Inhibits Cytochrome C Releasementioning
confidence: 99%
“…Exposure to UV radiation causes a complex cellular response, which includes the regulation of gene expression, DNA damage, lipid peroxidation and induction of apoptosis (Schwarz et al, 1995;Rosette and Karin, 1996;Sheikh et al, 1998;Glenn McGregor, 1999;Wikonkal and Brash, 1999). UV radiation, causing DNA damage by either direct interactions or by indirect pathways, may play a pivotal role in the process of carcinogenesis (for a recent review, see de Gruijl, 2000).…”
Section: Introductionmentioning
confidence: 99%